O Sonho de Ícaro: ensino de matemática mediado por tecnologia no ensino médio - Município de Manaus - Melo, Elzineide Ramos de (2019)
The research deals with technology-mediated learning in high school, with direct observation of the math discipline. The general objective was to analyze the teaching in the Technology-Mediated On-campus High School Program and its implications on the academic life of the 3rd year high school students in the mathematics discipline, in a rural school in the city of Manaus. The methodological tracking was based on a qualitative, exploratory approach, ethnographic nature and case study, using as forms of technical approaches to document analysis, participant observation, interviews and questionnaires, aiming at greater dynamics to data collection. It is noteworthy that the data collection also had an application of a test for students of the 3rd year of high school, according to the mathematical content taught, in order to understand how this teaching is being learned and reflected in the performance. from the students. Participated in this research professionals from the Media Center of the State Department of Education and Quality of Education of Amazonas - SEDUC and a school in the rural area of Manaus, standing out: principals, pedagogical advisors, teaching teachers of mathematics in teaching middle school, students and classroom teacher of the 3rd year of high school in the subject of mathematics through high school. To analyze the data collected during a research, a content analysis proposed by Bardin (2009) was used, which allowed the understanding of how subjects understand mediated teaching in the educational context. The results evidenced as technological innovations are a reality that breaks with an image of the teacher as a transmitter of simple knowledge, giving rise to an image of a stimulator, for whom the student seeks his own knowledge. The use of breakthrough technologies as geographical barriers, making education reach distant communities, such as the agricultural municipalities of Amazonas, expanding their access to education.